Diabetes causal attributions among affected and unaffected individuals - Margaret K Rose; Kristi A Costabile; Sarah E Boland; Rachel W Cohen; Susan Persky (BMJ Open Diabetes Research & Care)
Objective The present study aims to describe and compare causal attributions for type 1 diabetes (T1D) and type 2 diabetes (T2D) among affected and unaffected individuals and to investigate the relationships among attributions, attitudes, and beliefs.Research design and methods Adults with no diabetes (N=458), T1D (N=192), or T2D (N=207) completed an online survey. Measures assessed diabetes conceptual knowledge, causal attributions for T1D and T2D, perceived control over diabetes onset, and favorability judgements of individuals affected by each type.Results Results indicate general agreement on causal attributions for T1D and T2D among all respondent groups, with some divergences by disease status. All respondents attributed both T1D and T2D to genetics, and genetic attributions were positively associated with favorability judgements of individuals with T2D, but not those with T1D.Conclusions This report sets the stage for investigations into how and why attributions for T1D and T2D differ and the implications of these differences including stigmatization of individuals with diabetes and diabetes-related self-concept. Additionally, this work can inform efforts towards clinical and public health education to prevent and optimize treatment of T1D and T2D.